Pengaruh Sustainability Report Disclosure terhadap Keinformatifan Laba Akuntansi dengan Kepemilikan Asing sebagai Variabel Moderating - Rommy Septia Arifin; Nurzi Sebrina (Universitas Negeri Padang, 2022)
This study aims to analyze the effect of sustainability report disclosure on the informativeness of accounting earnings with foreign ownership as a moderating variable. The informativeness of accounting earnings which is the dependent variable in this research is measured by the Earning Response Coefficient (ERC) value. Sustainability report disclosure which is the independent variable in this study is measured by the SRDI value, namely the disclosure index based on GRI G4 for the sample companies in the 2016 observation year and the 2017-2019 observation year using the GRI Standard index. Foreign ownership which acts as a moderating variable in this study is measured by the FS value, which is the result of the number of shares owned by foreign parties divided by the total outstanding shares. This study uses control variables, namely market to book ratio, leverage, and firm size. The population of this study were companies listed on the Indonesia Stock Exchange in 2016-2019 using a sampling method, namely the purposive sampling technique so that the final sample of this study was 60 companies. The analysis technique used is the technique of moderated regression analysis (MRA). Overall, the results of this study indicate that the sustainability report disclosure does not significant positive effect on the informativeness of accounting earnings. Foreign ownership has a significant positive effect in moderating the relationship between sustainability report disclosure and the informativeness of accounting earnings.